Di Balik Jeruji: Menggali Realitas Kekerasan Seksual terhadap Tahanan Wanita oleh Aparat Penegak Hukum ( kepolisian ) - Hunggu, Airel Hamu Lee; Syahrani, Adinda Nurul; Hosnah, Asmak Ul (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2025)
Abstract Sexual violence by police officers against female detainees is not only a violation of the law, but also a serious threat to the integrity and security of the individual, although it is expressly regulated in Article 285 of the Criminal Code. integrity and security of the individual, although it is expressly regulated in Article 285 of the Criminal Code regulating the act with the threat of severe punishment. Ironically, the practice often face obstacles in effective law enforcement, resulting in painful injustices. painful injustice. In this journal, an analysis of the legal and social aspects of such sexual violence with a focus on evaluation of the implementation of the code of ethics, as stipulated in the National Police Chief Regulation Chief of Police Regulation No. 14/2011 on the Professional Code of Ethics of the Indonesian National Police, in the field. Indonesia, in the field. This review also considers the social and social and psychological impact of the crime as well as efforts to ensure victims receive proper legal and psychological legal and psychological assistance, thus this journal seeks to make a significant contribution to improving justice and seeks to make a significant contribution in improving justice and safety of individuals while expanding public awareness of the importance of of legal protection for victims of sexual violence where victims of sexual violence will continue to carry the remembrance of the horrific event for the rest of their lives. Keywords: Sexual Violence, Police Code of Ethics Implementation, Social and Psychological Impacts Abstrak Kekerasan seksual oleh oknum polisi terhadap tahanan wanita bukan hanya merupakan pelanggaran hukum, tetapi juga ancaman serius terhadap integritas dan keamanan individu, meskipun diatur secara tegas dalam Pasal 285 KUHP mengatur tentang tindakan dengan ancaman hukuman yang berat. Ironisnya, praktiknya sering kali menghadapi hambatan dalam penegakan hukum yang efektif, menghasilkan ketidakadilan yang menyakitkan. Dalam jurnal ini, dilakukan analisis terhadap aspek hukum dan sosial dari kekerasan seksual tersebut dengan fokus pada evaluasi implementasi kode etik, sebagaimana diatur dalam Peraturan Kapolri Nomor 14 Tahun 2011 mengenai Kode Etik Profesi Kepolisian Negara Republik Indonesia, di lapangan. Tinjauan ini juga mempertimbangkan dampak sosial dan psikologis dari tindak pidana tersebut serta upaya untuk memastikan korban mendapatkan bantuan hukum dan psikologis yang layak, sehingga jurnal ini berupaya memberikan kontribusi signifikan dalam meningkatkan keadilan dan keselamatan individu sambil memperluas kesadaran masyarakat akan pentingnya perlindungan hukum bagi korban kekerasan seksual diama korban kekerasan seksual akan terus membawa kenangan mengenai peristiwa buruk itu selama hidupnya. Kata Kunci: Kekerasan Seksual, Implementasi Kode Etik Polisi, Dampak Sosial dan Psikologis